2018
DOI: 10.1073/pnas.1802831115
|View full text |Cite
|
Sign up to set email alerts
|

Controlling fracture cascades through twisting and quenching

Abstract: Fracture fundamentally limits the structural stability of macroscopic and microscopic matter, from beams and bones to microtubules and nanotubes. Despite substantial recent experimental and theoretical progress, fracture control continues to present profound practical and theoretical challenges. While bending-induced fracture of elongated rod-like objects has been intensely studied, the effects of twist and quench dynamics have yet to be explored systematically. Here, we show how twist and quench protocols may… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…Image recordings were performed using high-speed camera FASTCAM SA1.1 (Photron, Tokyo, Japan) with resolution of and shooting speed of 12,000 fps. Experiments showed that the first fracture usually took place at a point near the middle of the stick, and continued to behave secondary fractures after a certain time and distance from the point of first fracture, suggesting an approximation of 6–13 times stick thickness between the first and the second crack, which is in general accordance with data in Figure 10 when is chosen as the set value for the secondary fracture, and are also in good agreement with data reported in [ 15 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Image recordings were performed using high-speed camera FASTCAM SA1.1 (Photron, Tokyo, Japan) with resolution of and shooting speed of 12,000 fps. Experiments showed that the first fracture usually took place at a point near the middle of the stick, and continued to behave secondary fractures after a certain time and distance from the point of first fracture, suggesting an approximation of 6–13 times stick thickness between the first and the second crack, which is in general accordance with data in Figure 10 when is chosen as the set value for the secondary fracture, and are also in good agreement with data reported in [ 15 ].…”
Section: Resultssupporting
confidence: 91%
“…Figure 4 , Figure 5 and Figure 6 show the excited flexural waveform curves at progressive time coordinates, and we can figure out that at the very beginning of both distance and time the excited bending moment will rise to beyond its initial value, that is, at the very beginning as long as the flexural stress wave is excited, the secondary fracture is about to happen, provided that once the bending moment exceeds it initial value a secondary fracture will start up. However, experience and experiments from us and other scholars [ 11 , 15 ] suggest that the secondary fracture will take place at a point with some certain distance from the first fracture point, which reminds that the crack criterion of the secondary fracture should be not the same as the quasi-static first fracture.…”
Section: Resultsmentioning
confidence: 99%
“…The ABAQUS finite-element model (FEM) presented in this paper is based on the experiments of Heisser [24] under the conditions of humidity 21%−34% and temperature 21% − 26%. The length and radius of the spaghetti is L = 240mm and d = 0.75mm, respectively, and its density is ρ = 1.5 ± 0.1 g/cm 3 .…”
Section: Finite-element-model Analysismentioning
confidence: 99%
“…The trend of the number of fractured segments is the same as that in the experiments, but the number of fractured segments obtained by the experiment tends to three while that obtained by the FEM is between three and four. This may be caused by the boundary conditions imposed by the FEM being ideal and completely symmetrical, so the number of fractured segments tends to be even, so that there are more results that tend to produce four segments [24] . Different quench speeds have little effect on the limit curvature, which is consistent with Heisser's experimental results and conclusions, which verifies the reliability of the FEM.…”
Section: Simulation Verification Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation